1996
DOI: 10.1128/jvi.70.3.1602-1611.1996
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutagenesis of the human papillomavirus type 16 E2 transactivation domain reveals separable transcriptional activation and DNA replication functions

Abstract: The E2 gene products of papillomavirus play key roles in viral replication, both as regulators of viral transcription and as auxiliary factors that act with E1 in viral DNA replication. We have carried out a detailed structure-function analysis of conserved amino acids within the N-terminal domain of the human papillomavirus type 16 (HPV16) E2 protein. These mutants were tested for their transcriptional activation activities as well as transient DNA replication and E1 binding activities. Analysis of the stably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
62
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 60 publications
(70 reference statements)
10
62
0
Order By: Relevance
“…Our findings are consistent with previous observations for Y138. In an earlier study that analyzed HPV-16 E2 TAD mutants, Y138 was replaced by alanine and was found to be moderately impaired for transcriptional activation (40% to 80% of WT), DNA replication (10% to 40% of WT), and E1 binding (40% to 80% of WT), and exhibited reduced Brd4-CTD association (51,52). BPV Y138F bound E1, and although it could stimulate transcription and transient replication, it was not as active as the WT (22).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous observations for Y138. In an earlier study that analyzed HPV-16 E2 TAD mutants, Y138 was replaced by alanine and was found to be moderately impaired for transcriptional activation (40% to 80% of WT), DNA replication (10% to 40% of WT), and E1 binding (40% to 80% of WT), and exhibited reduced Brd4-CTD association (51,52). BPV Y138F bound E1, and although it could stimulate transcription and transient replication, it was not as active as the WT (22).…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in Figure A,C, W4H and W4H_Y6R peptides were also predicted to form hydrogen bonds with Glu39 of HPV16 E2. Glu39 of HPV16 E2 was previously reported as an essential amino acid residue for replication function of E2 . The corresponding residue of Glu39 of HPV16 E2, Glu43 of HPV18 E2, is in a favorable ionic interaction with Arg454 of HPV18 E1; and mutation of Glu43 of HPV18 E2 or Arg454 of HPV18 E1 has previously shown to result in a significant reduction of E1–E2 complex formation …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, disruption of this complex could possibly inhibit viral propagation. A mutated E2, which was defective for E1 binding, has been shown to lose its DNA replication function . In the previous study, dodecapeptides that could bind to HPV16 E2 were screened from the phage display library .…”
mentioning
confidence: 99%
“…However, the specific function(s) of E2 affected by these mutations is not known. Our assessment of the in vitro hTFIIB binding activities of HPV-16 E2 missense mutants that were previously shown to be defective for transactivation (48) has revealed no quantitative change in hTFIIB binding activity (28a). It is possible that these mutants are defective for another essential E2 function that is unrelated to TFIIB interaction.…”
mentioning
confidence: 90%
“…Full-length BPV-1 E2 and E2-TR are indicated. 13,48). However, the specific function(s) of E2 affected by these mutations is not known.…”
mentioning
confidence: 99%